(untitled) (Research, Society and Development, 2022)
Amorphous solid dispersions (ASDs) are a viable alternative to enhance the kinetic solubility of poorly water-soluble drugs. However, there is lack of discussion about the impact of drug loading on dissolution rate and drug diffusion across the membrane generated by supersaturation. So, it was obtained amorphous solid dispersions with nevirapine and polyvinylpyrrolidone K-30 by solvent evaporation method using different drug loadings (10%, 15% and 20% w/w). Thermal analysis, Fourier transform infrared spectroscopy and x-ray diffraction characterized the ASDs, indicating that there was a good miscibility between components which stabilized the drug in its amorphous state. The intermolecular interactions impacted on the ASDs in vitro performance, where they were evaluated to dissolution tests under different conditions and permeability studies. All amorphous systems had an increment in aqueous solubility compared to nevirapine alone, although 10% amorphous solid dispersion (SD 10) kept drug supersaturation at very high concentrations longer, preventing the drug recrystallization, having the greater drug flux on membranes and more intermolecular interactions among the components. Therefore, large quantities of the polymer are required for the stability of the amorphous drug, due to the increase in the number of intermolecular interactions.